Geophysical study of Hammam Sidi Maamar geothermal site in Central Tunisia for sustainable development - Azaiez, H.; Gabtni, H.; Chabaane, A.; Sayem, G.; Bédir, M. (Journal of African earth sciences (1994), 2020)
Geophysical methods provide important help to investigate geothermal reservoirs. They permit to delineate deep and near surface structuring and to appreciate fluid circulation. In this study, we performed an integrated geophysical study using regional seismic reflection profiles and local Electrical Resistivity Tomography (ERT) data analyses to identify the relation between faults and specific geothermal pathways around Hammam Sidi Maamar thermal spring site in Hajeb Layoun area (Central Tunisia). The proposed geological model performed from seismic reflection composite sections reveals the geometry in depth series of the Lower Cretaceous from the recharge zone (Jebel Mrhila mountain) to the emergence area of Hammam Sidi Maamar (Jebel Baten Damous mountain) and traces the path of the thermal water, from its recharge area till surfacing, in order to propose a new suitable intake location with higher flow and temperature. The results of seismic and ERT data analysis confirm that the Hammam Sidi Maamar geothermal site is tectonically related to the junction of the NE-SW Baten Damous fault corridor and the NW-SE to E-W northern fault corridor of Hajeb Layoun graben. The water is charged from Lower Cretaceous (Hauterivian to Aptian) outcrop series in Jebel Mrhila Mountain to the West. It flows into the carbonate reservoir below the Hajeb Layoun-Jelma Plain, where the Lower Cretaceous reservoirs are reaching more than 2500 m deep. The reservoir geologic layers show ascent geometry towards Jebel Zaouia Mountain then they sink into the Hajeb Layoun Graben to the East. The thermal water rises to surface thanks to the deep faults that affect the Lower Cretaceous reservoir and the geologic series above. High resolution Electrical Resistivity Tomography panels, we carried out in Hammam Sidi Maamar geothermal site, allowed to locally identify the faulting architecture which controls the flow of hot water. Firstly, filtering and processing of ERT data were performed. 2D ERT modeling, mapping and 3D ERT view interpretation, were also performed to more understand the local tectonic/geothermal flow setting. Finally, to identify the prominent site for lateral and vertical geothermal flow plumes, we propose to drill 50 m–60 m intake well associated with a tectonic junction of the NE-SW Baten Damous fault corridor and the NW-SE to E-W Hajeb Layoun graben fault. •This is an integrated geophysical study using Seismic Reflection/Electrical Resistivity Tomography investigation, in a low temperature geothermal context.•Seismic Reflection allowed exploring, in a regional scale, the geometry and the structuring of the deep carbonate reservoir which is affected by major faults that serve as the primary conduit for rising water circulation.•2D ERT modeling, mapping and 3D ERT view interpretation, were performed to more understand the local tectonic/geothermal flow setting and to identify the prominent site for lateral and vertical geothermal flow plumes.